Effect of Genotype and Culture Media on Callus Induction and Plant Regeneration from Matured Rice Grain Culture - Niroula, RK; Sah, BP; Bimb, HP; Nayak, S (Journal of the Institute of Agriculture and Animal Science, 2005)
This study was under taken to elucidate the effect of genotypes and media compositions on callus induction from mature rice seeds. Three different callus induction media, designated as A (N6 mineral salts + N6 vitamins, 2 mg/l each + myoinositol, 100 mg/l + 2,4-D, 2.5 mg/l + kinetin, 0.5mg/l + AgNO3, 10 mg/l + maltose, 50 gm/l); B (MS organic salts + N6 mineral salts + NAA, 4 mg/l + kinetin, 2 mg/l + AgNO3, 5mg/l and sucrose, 60 gm/l); and C (B media without AgNO3), and six rice genotypes viz. Jumlimarshi, Tilki, Jethobudo, Manshara, Masuli and Pahenle were evaluated. The modified N6 medium supplemented with 2, 4-D, 2.5 mg/l and AgNO3, 10 mg/l exhibited better performance in callus induction. Among genotypes, callus induction frequency was higher (100%) in Masuli, Tilki and Jumlimarshi regardless of media tested. The positive effect of AgNO3 was only observed in medium A for quality callus induction and subsequent plant regeneration. The genotype Tilki performed better regarding plant regeneration (27.77%). Therefore, it is suggested that application of medium A is advantageous to accomplish overall efficiency of callus induction and plant regeneration from seeds of various rice genotypes. Key words: 2, 4-D; AgNO3; dehulled rice; in vitro; regeneration J. Inst. Agric. Anim. Sci. 26:21-26 (2005)